2003
DOI: 10.1381/096089203322618605
|View full text |Cite
|
Sign up to set email alerts
|

Depression Score Predicts Weight Loss following Roux-en-Y Gastric Bypass

Abstract: Our data show a positive correlation between pre-surgical severity of depression as measured by BDI score and the 1-year success at weight loss after RYGBP as measured by %EWL. More depressed individuals tend to lose greater amounts of weight compared with less depressed individuals. Future prospective studies should examine possible mechanisms and effects of depression and other psychiatric disturbances on long-term weight loss after RYGBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
3
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 13 publications
3
102
3
5
Order By: Relevance
“…This scale has received considerable support in its validity and reliability, including adequate internal consistency and test-retest reliability (36,37). The BSQ, BDI, and RSES are widely used measures of body image dissatisfaction and general psychosocial functioning in diverse clinical samples of obese patients (38)(39)(40)(41)(42), including bariatric surgery patients (43)(44)(45)(46)(47), and have been found to be associated with eating-related pathology within this latter group (25,26,48,49). The EOQ was included as an additional exploratory measure since eating (or overeating) in response to emotions is not uncommon for individuals who struggle with their eating behavior.…”
Section: Procedures and Assessment Measuresmentioning
confidence: 99%
“…This scale has received considerable support in its validity and reliability, including adequate internal consistency and test-retest reliability (36,37). The BSQ, BDI, and RSES are widely used measures of body image dissatisfaction and general psychosocial functioning in diverse clinical samples of obese patients (38)(39)(40)(41)(42), including bariatric surgery patients (43)(44)(45)(46)(47), and have been found to be associated with eating-related pathology within this latter group (25,26,48,49). The EOQ was included as an additional exploratory measure since eating (or overeating) in response to emotions is not uncommon for individuals who struggle with their eating behavior.…”
Section: Procedures and Assessment Measuresmentioning
confidence: 99%
“…However, depression has not been a prognostic indicator of overall failure based on % EWL, psychosocial function, or quality of life (Kalarchian et al, 2005;Ma et al, 2006;SwanKremier, 2005). Some have reported that it may actually promote greater short-term weight loss (Averbukh et al, 2003;Ma et al, 2006). …”
Section: What Is Known -Paradoxical Resultsmentioning
confidence: 99%
“…140 This figure used with permission of publisher. 139 Bariatric surgery for pediatric extreme obesity TH Inge et al medical complications, less weight loss, 171,172 and less relative improvement in social functioning, quality of life, depression and overall psychological status. Our early observations in a sample of 16 adolescents (mean age 15.6 years; 63% females, mean BMI 59.9 kg/m 2 ) revealed that at 12-months postsurgery adolescents experience significant improvement in HRQOL and depressive symptomatology (e.g., within more normative ranges) despite continued obesity (mean BMI 36.9 kg/m 2 ; Zeller, M, unpublished data).…”
Section: Psychosocial Implications Of Obesity In Children and Adolescmentioning
confidence: 99%